Power and Powerlessness in a Group Based Digital Story Telling Project-An Exploration of Community Perceptions of Health Concerns in Urban Malawi - Nyirenda, Deborah; Payesa, Chipiliro; Ntaba, Jolly; Mhango, Rachel; Kingori, Patricia; Parker, Michael; Desmond, Nicola (Frontiers in Public Health, 2022)
Digital Story Telling (DST) is an art-based research method used to explore embodied experience of health and initiate dialogue with under-represented groups on issues affecting them. It involves engaging participants to create and share their stories using photos, drawings, and audio recordings in short videos. Benefits of DST include enhancing co-creation of knowledge, empowering participants to confront dominant narratives and revise inaccurate representations. We report our experiences and reflections of using DST to explore community perceptions of health concerns in urban Malawi. Community leaders were briefed about the project before and after study related activities. Three participatory workshops were organized to train community members in DST, support them to develop videos and discuss their experiences of DST. Twenty-six participants from two high density urban communities consented to be part of the workshops. They were all new to DST. All the 26 participants were invited together to the three workshops and their DSTs were developed in smaller groups (n = 7), based on their geographical location. Although we engaged residents from selected communities to share priority health concerns, all the seven groups presented challenges pertaining to Water, Sanitation and Hygiene (WASH), and their powerlessness to address the complex challenges. The collective focus on WASH showed that DST effectively empowered communities to present priority health concerns. The inability of community members to address the challenges without external assistance or failure to use findings from DST to generate social change however raise questions on the ideals of empowerment and social justice. In addition, lack of financial resources or technical know-how to produce digital stories and unequal power relationships between service providers and community, may affect the use of DST for community activism among socio-economically disadvantaged groups. We conclude that DST empowered participants to articulate genuine health challenges that they felt powerless to address. We question the realization of “empowerment” and social justice of vulnerable participants in cases where structural challenges present obstacles to effectively address social inequalities.